182k views
0 votes
X(x+1) = -3


I am wondering how to simplify this using distributive principal

1 Answer

4 votes

Answer:

x² + x + 3 = 0

Explanation:

To use the distributive property, we want to multiply the coefficient (the number directly outside the parentheses) with each term within the parentheses.

x(x + 1) = -3

Distributive property:

x • x = x²

x • 1 = x

This results in:

x² + x = -3

Add 3 to both sides.

x² + x + 3 = 0

This is the equation simplified.

Hope this helps!

User Sujee
by
5.6k points